Model Quadruple Helix Dalam Pengembangan UMKM (Studi Kasus Pada Industri Pisang Sale Kutacane Kab. Aceh Tenggara) - Muslim Marpaung; Sugianto Sugianto; Ulfa Yolanda (ITB AAS INDONESIA Surakarta, 2021)
This study aims to obtain a comprehensive picture of the synergy of banana sale stakeholders in Kab. Southeast Aceh. The Quadruple Helix model is one suitable model for social research and innovation. This study uses a qualitative research design with a phenomenological approach that seeks to understand the perspectives, thoughts and experiences of stakeholders regarding the synergy of Quadruple Helix stakeholders in realizing the development of the banana sale business in Kab. Southeast Aceh. The results show that there are a number of problems related to synergy in the development of banana sale in Kab. Aceh Tenggara is partly because there is no common vision of stakeholders and cooperation and coordination between banana sale business actors, the government and stakeholders. Each stakeholder translates the sale of bananas, causing a debate on how to develop the sale of bananas in the future. In particular, the government should pay special attention to banana sale managers equally to develop the banana sale business and support from the wider community. The key to the successful implementation of the banana sale business development in Kab. Aceh Tenggara, among others, unity of mission, joint commitment and coordination among stakeholders.